Effect of the chronological age and sexual maturation on the time to exhaustion at maximal aerobic speed - Machado, F. A. [UNESP]; Guglielmo, L. G. [UNESP]; Denadai, B. S. [UNESP] (My University, 2007)
The purposes of this study were: a) to verify the effect of chronological age and sexual maturation on the time to exhaustion at VO2max (t lim) and; b) to examine the reproducibility of tlim in boys aged 10-15 years. Forty boys, divided into 4 groups, in accordance to the chronological age (G10-12 and G13-15) and sexual maturation (P1-P3 and P4-P5 levels for pubic hair), performed the following tests: 1) incremental test for determination of VO2max and; 2) all-out exercise bout performed at VO2max to determine the tlim. There was no difference of tlim (sec) between G10-12 and G13-15 (181.5±96.3 vs. 199±105.5). While the two measures of tlim were moderately related (r=0.78), tlim from the second test (226.6±96.1 s) was higher than that of the first (191.3±79.2 s). We can conclude that the tlim is not influenced by chronological age and sexual maturation. Besides, tlim presents a lower reproducibility in children and adolescents.
Keywords: Children; Maximal oxygen uptake; Running